COMPLIANCE WITH TAKING FE TABLETS IN THIRD TRIMESTER PREGNANT WOMEN AT PUSKESMAS CIAWI - Sobari, Dika Maretika; Dewi Purnamawati (Muhammadiyah International Public Health and Medicine Proceeding, 2022)
Anemia in pregnant women is an iron deficiency experienced by pregnant women, anemia in pregnant women can increase the risk of bleeding in childbirth and the birth of low birth weight babies (LBW). One of the efforts to reduce the incidence of anemia in pregnant women is by giving 90 tablets of Fe during pregnancy. This study aims to obtain an overview of the compliance of pregnant women in consuming Fe tablets at the Ciawi Health Center. In qualitative descriptive research, informants in this study were 7 (seven) people consisting of 3 (three) third-trimester pregnant women, 2 (two) patients' families, and 1 (one) midwife. Data were collected through in-depth interviews, data were analyzed descriptively. The results showed that less than half of the informants were obedient in consuming Fe, the reason the informants did not consume Fe was due to the effects of nausea caused when consuming Fe and based on previous experiences of pregnant women who did not regularly consume Fe.